An Investigation on the Evaluation and Improvement of Existing Features of Foot Exercise Apparatus Designed for Use in Evertor and Invertor Muscle Dysfunction - Osman Nuri Özyalvaç; Serap Yeşilkır Baydar; Ufuk Ateşoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Clubfoot deformity is one of the most important congenital anomalies of paediatric orthopaedics and characterised by equinus, supination and inversion of the foot muscles. Although treatment of this pathology, which presents as a gait disorder in the early stages of development, is currently attempted with exercise, physiotherapy and/or surgical approaches, the success rates of these treatments are low and/or lateral compression recurs. This situation confronts many children and their families with the difficulties and costs of the treatment process. The aim of this study is to produce and develop an apparatus for the treatment of this dysfunction with today's engineering approaches. For this purpose, in this study, a prototype was designed and manufactured using three-dimensional (3D) printing method with tough polylactic acid (PLA). The prototype can support both the right and left foot and enables to exercise up to angles of 31.8° for both evertor and invertor muscle. Clubfoot deformity is one of the most important congenital anomalies of paediatric orthopaedics and characterised by equinus, supination and inversion of the foot muscles. Although treatment of this pathology, which presents as a gait disorder in the early stages of development, is currently attempted with exercise, physiotherapy and/or surgical approaches, the success rates of these treatments are low and/or lateral compression recurs. This situation confronts many children and their families with the difficulties and costs of the treatment process. The aim of this study is to produce and develop an apparatus for the treatment of this dysfunction with today's engineering approaches. For this purpose, in this study, a prototype was designed and manufactured using three-dimensional (3D) printing method with tough polylactic acid (PLA). The prototype can support both the right and left foot and enables to exercise up to angles of 31.8° for both evertor and invertor muscle.